Answer:
The initial velocity of spaceship P was u₁ = 5.06 m/s
Step-by-step explanation:
In an elastic collision between two bodies the expression for the final velocity of the second body is given as follows:
![V_(2) = ((m_(2)-m_(1)) )/((m_(1)+m_(2)))u_(2) + (2m_(1) )/((m_(1)+m_(2)))u_(1)](https://img.qammunity.org/2021/formulas/physics/college/16o3jz7rturunmdbqiygi5zjowv16o6l86.png)
Here, subscript 1 is used for spaceship P and subscript 2 is used for spaceship T. In this equation:
V₂ = Final Speed of Spaceship T = 8.1 m/s
m₁ = mass of spaceship P = 4 M
m₂ = mass of spaceship T = M
u₁ = Initial Speed of Spaceship P = ?
u₂ = Initial Speed of Spaceship T = 0 m/s
Using these values in the given equation, we get:
![8.1 m/s = (M-4M )/(4M+M)(0 m/s) + (2(4M) )/(4M+M)u_(1)](https://img.qammunity.org/2021/formulas/physics/college/2q377frdykjpdqj91w78lu8rbdu9rxgz9q.png)
8.1 m/s = (8 M/5 M)u₁
u₁ = (5/8)(8.1 m/s)
u₁ = 5.06 m/s